Thinking ethically about pandemics a matter of public health and social ethics - Smith, Patrick T. (2020)
This essay argues that any ethical approach to mitigating the negative effects of pandemics must give detailed and sustained attention to those who are on the margins of society. This means tackling widespread racism and concentrated poverty in our body politics. The challenges resulting from pandemics are not merely ones of public health but are simultaneously matters of social ethics. The aim of this essay is to highlight important values from religious social ethics for responding ethically to pandemics. In this work, I do not undertake the task of formulating and prescribing national policies that egalitarian democratic societies should adopt in pandemic situations. Instead, the paper focuses on how religious social ethics can help reimagine social life and communal practices by focusing on the margins to mitigate some of the negative effects caused by public health disasters.
Keywords: Health Disparities; Poverty; Racism; Social ethics. Pandemic ethics; Social Justice